2014
DOI: 10.2147/ijn.s62630
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and optimization of primaquine-loaded solid lipid nanoparticles

Abstract: Primaquine (PQ) is one of the most widely used antimalarial drugs and is the only available drug that combats the relapsing form of malaria. PQ use in higher doses is limited by severe tissue toxicity including hematological- and gastrointestinal-related side effects. Nanoformulation of drugs in an appropriate drug carrier system has been extensively studied and shown to have the potential to improve bioavailability, thereby enhancing activity, reducing dose frequency, and subsequently reducing toxicity. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…Also, at the end of the test, about 4%-5% of the ash was remained and the rest of the ingredients were completely decomposed. These results are consistent with the results reported in the literature (Ismail et al, 2014;Omwoyo et al, 2014;Prabhu et al, 2015;Rafi Shaik et al, 2017).…”
Section: Tg/dta Ft-ir and Xrd Studysupporting
confidence: 94%
“…Also, at the end of the test, about 4%-5% of the ash was remained and the rest of the ingredients were completely decomposed. These results are consistent with the results reported in the literature (Ismail et al, 2014;Omwoyo et al, 2014;Prabhu et al, 2015;Rafi Shaik et al, 2017).…”
Section: Tg/dta Ft-ir and Xrd Studysupporting
confidence: 94%
“…TGA analysis is used for nanoparticle characterization and indicates degradation behavior of formulations [38]. Herein, we found that RSV has undergone thermal degradation after approximately 250°C, similarly to previous observations [39].…”
Section: Resultssupporting
confidence: 86%
“…DSC and XRD are complementary techniques that evaluate the thermal behavior and crystallinity, respectively, and provide valuable information for characterization of loaded liposomes [46,51,52]. DSC evaluates the differences in heat flow (electric power) between a sample and a reference.…”
Section: Differential Scanning Calorimetry (Dsc) and X-ray Diffractiomentioning
confidence: 99%
“…The heat flow curve provides the respective transition temperature and enthalpy, which allows to identify the nature of thermal events: endo-or exothermic [53][54][55]. DSC represents the most useful thermal analysis technique in the study of lipid-based materials [46,52,[54][55][56].…”
Section: Differential Scanning Calorimetry (Dsc) and X-ray Diffractiomentioning
confidence: 99%
See 1 more Smart Citation